Effects of different baits on monofilament gillnet effectiveness in a freshwater reservoir fishery (Keban Dam Lake, Turkey) - Dartay, M.; Duman, E. (Wiley-Blackwell, 2016)
Aim of this study was to test the gillnet efficiency in Keban Dam Lake using different baits as attractants. Gillnets of 50 m length (stretched mesh sizes: 40, 50, 55 mm) were employed between January 2009 and December 2010 in the study. Two types of grain (corn and wheat) as well as processed plant material (beet cake) and animal livers were tested as bait to attract both carnivorous and omnivorous species. The catching efficiency of baited and non-baited gill nets was compared. Overall, a total of 358 fish from eight different species were caught in baited gillnets, whereas only 189 fish were caught with non-baited gillnets. Most fish (55.90%) were caught with corn, wheat or beet cake as bait; the fewest (59 fish, 9.96%) were captured with animal liver. About 34.1% were caught with non-baited gillnets. By species, Capoeta trutta (Cyprinidae) was most frequently captured. In conclusion, the gillnets bated with corn, wheat, and beet cake yielded higher catches (P < 0.05) than did the nonbaited monofilament gillnets.
1st International Fisheries Symposium -- MAR 24-27, 2013 -- Girne, CYPRUS
Keywords: Catch Rates; Nets